PENERIMAAN DIRI ORANG TUA MELALUI DUKUNGAN KELUARGA TERHADAP ANAK BERKEBUTUHAN KHUSUS - Asiah, Asiah; Meliani, Lisah; Herlinawati, Herlinawati; Hidayat, Abas (Jurnal Keperawatan Karya Bhakti, 2025)
The process of accepting the condition of children with special needs requires family support. Self-acceptance of children is an important aspect that parents need to have. Parents often show various reactions when dealing with children with special needs. One response that usually arises is to give high demands or expectations to children, which can be a sign that they have not entirely accepted the child's condition. This phenomenon is known as denial or rejection of the reality experienced. The study aimed to determine the relationship between family support and self-acceptance of parents of children with special needs in S.L.B. Quantitative research design with a Cross-Sectional approach. The population of 40 parents with children with special needs in S.L.B. used total sampling to obtain a total sample of 40 people. The research instrument was a family support and self-acceptance questionnaire. Data analysis was carried out using the Spearman Rank test approach method. The study results showed that family support had a sufficient category of 20 respondents (50%). The self-acceptance of parents with special needs children was obtained in the high category of 15 respondents (37.5%). The statistical test results obtained a p-value of 0.018 (<0.05), indicating a relationship between family support and self-acceptance of parents with children with special needs in S.L.B. Suggestions for parents who have children in S.L.B. should socialize more often with family, relatives or the surrounding environment so that they can provide support and motivation to increase self-acceptance and continue to explore their child's potential so that parents are more accepting of their child's condition. Keywords: Family Support; Self Acceptance; Children with Special Needs